(3JaSjQ GdbQBfs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3Udi Gddg Ydi SjOfG eMeO hYdjg JSdjekG s
(3BNQgG (B:s
(3hJPcQ HbjI JaSjQfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B438s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs